Features of Mechanical Characteristics of Sand-Clay Mixtures in the Production of a Particularly Responsible Purpose Steel Castings (Texas Journal of Engineering and Technology, 2022)
The formation of sand-clay mixtures (SCM) has become widespread at enterprises producing large-size casting. SCM is a mixture of quartz sand with astringent clay, water and process additives, which can take the form of the necessary configuration when pressed, shaken, inflated and other effects. After casting and solidification of castings, the mold is subject to destruction, its material is prepared for subsequent reuse. At the same time, it is necessary to introduce an additional portion of clay and process additives into the mixture instead of used ones, as well as remove part of the mixture. Researches of moulding sand-clay mixtures of various compositions are presented in this article. A comparative analysis aregiven. The effect of starch on the mechanical properties of the mixture has been researched